EFFICIENCY OF COMPLEX PATHOGENIC APPROACH FOR TREATMENT OF PATIENTS WITH NONALCOHOLIC STEATOHEPATITIS COMBINED WITH TYPE 2 DIABETES MELLITUS - Pavlovskyi, S. (The Ukrainian Scientific Medical Youth Journal, 2018)
Aim is to optimize treatment of non-alcoholic fatty liver disease (NAFLD) combined with type 2 diabetes mellitus. 100 patients with NAFLD in stage of non-alcoholic steatohepatitis (NASH) were enrolled into study. Application of S-adenosylmethionine during the treatment of patients with non-alcoholic fatty liver disease (NAFLD) had high efficacy in the normalization of the functional, biochemical and cytokine profile of the blood. Combination of gliclizide and pioglitazone led to the decrease in the levels of cytolysis and mesenchymal-inflammatory syndromes, stabilization of lipid metabolism. This fact confirms the positive lipotrophic effect of the complex effect of gliclizide and pioglitazone on the functional state of hepatocytes, indicates decrease in insulin resistance and improves cell function. Complex therapy with combination of hypoglycemic and lipotropic drugs (gliclizide, pioglitazone, S-adenosylmethionine) showed good results, confirming the positive complex effect of S-adenosylmethionine, gliclizide and pioglitazone on the functional state of hepatocytes, led to decrease in insulin resistance and production of antiinflammatory effect. Pain syndrome remained significant in 9 patients (30%, 1.8 times less than before treatment); dyspeptic syndrome – in 10 patients (33,3%, decreased by 1,7 times), anorexia – in 10 patients (33,3%, a decrease of 1,9 times), asthenia – in 11 patients (36,7 %, decrease by 1.9 times). Combination of hypoglycemic, lipotropic therapy and basic therapy positively influenced on the state of hepatocytes decreasing activity of ALT, AST, alkaline +phosphatase. USG study showed reduction of the hepatic tissue changes compared to the visualization results before treatment. Particularly important was a significant decrease in the number of patients on the stage 3 of hepatosis having a decrease in the levels of TNF-α, IL-6 and C-reactive protein and increase of adiponectin. According to the results, application of the proposed agents affecting specific pathogenic links of NAFLD is believed to be an effective way to treat NAFLD.